PENGEMBANGAN MODUL PELATIHAN PENGENALAN DASAR BAHASA PEMROGRAMAN JAVA DENGAN MODEL ARCS - Yudertha, Andreo - (Computer Based Information System Journal, 2021)
1048 / 5000 Translation results The introduction of programming languages ​​to students is very rare. As a solution for the introduction of programming languages ​​for students is to hold training and workshops for students. The training module was developed by applying the ARCS (Attention, Relevance, Confidence and Satisfaction) model with the aim of increasing students' motivation to learn programming languages ​​further. The resulting module was applied to the training carried out for students of SMA Negeri 10 Jambi City. There were 30 participants, consisting of grade 10 and grade 11 students. Participants were mentored by 4 instructors who were also observers. The ARCS model can be used as a reference in developing Java programming training modules with the aim of motivating and enthusiastic students. The module has been used in basic java programming training at SMA 10 Jambi City, with observations (scale 100), for an average student attention of 91.25, participation 94, persistence 93.25, task completion 83.25, and activeness 93.5.